Interfacial Softening and Electrolyte Uptake in Co3O4 OER Catalysts: Insight from Operando Spectroscopy and Fast EQCM‐D - Leppin, Christian; Placke‐Yan, Carsten; Bendt, Georg; Hernandez, Sheila; Tschulik, Kristina; Schulz, Stephan; Linnemann, Julia (ChemCatChem)
Cobalt spinel (Co3O4) catalysts are widely studied in scope of the electrocatalytic oxygen evolution reaction (OER), yet the role of interfacial structural transformation under anodic bias remains under debate. Here, we employ an operando approach, combining a fast electrochemical quartz crystal microbalance with dissipation monitoring (EQCM-D), electrochemical impedance spectroscopy (EIS), and Raman spectroscopy to investigate interfacial transformations of Co3O4 nanoparticle electrodes in alkaline electrolyte. We identify two distinct regimes during the anodic sweep prior to the macroscopic OER onset. At lower potentials, the catalyst interface remains mechanically rigid while reversibly associating several OH−/H2O species per oxidized cobalt site. At higher potentials, pronounced softening of the interface occurs alongside further uptake of electrolyte species. This indicates amorphization and a ‘swelling process’ beyond simple adsorption. Notably, an electrochemical conditioning treatment can suppress mass and compliance hysteresis without affecting OER activity, suggesting that most incorporated electrolyte species do not participate in the OER. EIS further reveals that OER intermediates form well below the apparent OER onset potential. These results advance our mechanistic understanding of interfacial transformations in cobalt-based OER catalysts and establish EQCM-D as a sensitive operando technique for probing electrocatalyst transformations.
Keywords: electrocatalysis; Co3O4; EQCM-D; OER

Role of Defects in Reversible Surface Restructuring and Activity of Co3O4 Oxygen Evolution Electrocatalysts - Scharf, Carl Hendric; Chandraraj, Alex; Dyk, Konrad; Stebner, Felix; Lepin, Sören; Tian, Jing; El Bergmi Byaz, Laila; Stettner, Jochim; Leppin, Christian; Kotova, Anastasiia; Reinke, Sebastian; Linnemann, Julia; et al. (ACS Catalysis)
Overcoming the slow kinetics of the oxygen evolution reaction at the anode is a key challenge for the production of hydrogen via electrolysis. This reaction operates at very positive potentials, where the electrocatalyst is exposed to highly oxidative conditions and prone to potential-dependent transformation of the near-surface region. While substantial evidence for such surface restructuring exists, its extent and relevance for the catalyst’s activity are unclear. We address this topic for the case of Co3O4, one of the best-known electrocatalysts exhibiting surface restructuring, by studies of epitaxial (111)-ordered electrodeposited films with combined operando X-ray surface diffraction and absorption spectroscopy, electrochemical impedance spectroscopy, and electrochemical measurements on rotating disk electrodes. Comparison of the as-prepared and annealed state of the same samples, which both are stable even under long-term oxygen evolution conditions, provides clear insight into the role of surface defects. Our results show that defect-free annealed Co3O4(111) surfaces are structurally stable over a wide potential range and hydroxylate via adsorption at surface oxygen and Co sites. Potential-induced surface restructuring of the Co3O4 lattice occurs only in the presence of surface defects, leading to the formation of the well-known nanometer-thick oxyhydroxide skin layer. The presence of this skin layer promotes oxygen evolution at low overpotentials but results in higher Tafel slopes. As a result, highly ordered Co3O4(111) surfaces are more active at high current densities than defective Co3O4 surfaces that undergo surface restructuring. These results highlight that strategies for catalyst surface defect engineering need to be application-oriented.
Keywords: electrocatalysis; oxygen evolution reaction; cobalt spinel; operando characterization

Nanocellulose Membranes for Plasmon-Enhanced Removal of Organic Pollutants from Water - de Souza, Sivoney Ferreira; Beresowski, Christina; Kosmella, Sabine; Ameixa, João; Pothineni, Bhanu Kiran; Keller, Adrian Clemens; Hartlieb, Matthias; Taubert, Andreas; Bald, Ilko (ACS Applied Nano Materials)

On the role of cation-DNA interactions in surface-assisted DNA lattice assembly - Xu, Xiaodan; Pothineni, Bhanu Kiran; Grundmeier, Guido; Tsushima, Satoru; Keller, Adrian Clemens (Nanoscale)
Surface-assisted DNA lattice assembly is used in the synthesis of functional surfaces and as a model of supramolecular network formation. Here, competitive DNA binding of different cation species is investigated...

Mechanisms of deposit formation in injection moulding cavities and the role of tool coatings and internal release agents - Lingnau, Kai; Theile-Rasche, Chantal; Vissing, Klaus; Moritzer, Elmar; Grundmeier, Guido; Wiesing, Martin (Surface and Coatings Technology)
Keywords: Plasmabeschichtung; Spritzgießen; Spritzgießwerkzeug; Trennschicht; ultraTrenn; Werkzeugbeschichtung

Stability of Information‐Carrying DNA Origami Nanostructures During Repeated Freeze–Thaw Cycles - Li, Xinyang; Rabbe, Lukas; Linneweber, Jacqueline; Grundmeier, Guido; Keller, Adrian Clemens (Chemistry–Methods)
Encoding information in molecular arrangements on DNA origami nanostructures (DONs) provides the basis for novel concepts in molecular data storage and computing. To preserve their integrity over long timescales, the information‐carrying DONs are often stored in a frozen state. Here, we investigate the effect of repeated freeze–thaw (F/T) cycles on the structural and functional integrity of DONs carrying biotin (Bt) modifications. Streptavidin (SAv) binding is used to visualize the stored information by atomic force microscopy (AFM) before and after 40 F/T cycles. Two strategies are compared by F/T cycling of (I) SAv‐bound DONs and (II) SAv‐free DONs that are exposed to SAv directly before AFM imaging. Our results reveal that while the DONs retain their overall shape, F/T cycling induces a small amount of damage, leading to slightly reduced SAv binding. Adding glycerol at mM concentrations efficiently protects the DONs and restores the original SAv binding yields. Nevertheless, SAv exposure after F/T cycling leads to slightly higher and more consistent SAv binding yields and a lower background of nonspecifically adsorbed SAv compared to Strategy I. This makes information readout by AFM more efficient and renders Strategy II more convenient for long‐term storage of information‐carrying DONs with repeated information readout.

Molecular lithography with DNA nanostructures: Methods and applications - Keller, Adrian Clemens; Linko, Veikko (Journal of Physics D: Applied Physics)
Abstract Lithographic surface patterning is a cornerstone of modern materials and device fabrication. Although the available lithography techniques are constantly being advanced to push the feature sizes down to the few-nanometer scale, such developments are associated with many technological and economic challenges. Combining established top-down lithography with bottom-up self-assembly strategies has the potential to overcome those challenges and enable the manipulation of matter with molecular precision. One of the most exciting approaches in this regard is to harness the programmability of DNA self-assembly to create precise DNA nanostructure masks to be used in the lithographic patterning of diverse substrates. DNA nanotechnology has provided us with a versatile toolbox for the high-yield synthesis of 2D and 3D nanostructures with complex, user-defined shapes at unprecedented molecular accuracy. Consequently, the last decade has seen intense research efforts aimed at transferring such DNA nanostructure shapes into functional organic and inorganic materials and we have now arrived at a point where sophisticated molecular lithography approaches utilize DNA nanostructure masks for the fabrication of plasmonic surfaces for metamaterials and sensing applications. This review summarizes how the spatial information of such DNA nanostructure masks can be transferred into various organic and inorganic materials through selective etching and deposition steps. The review also discusses recent developments toward all-purpose molecular lithography schemes and highlights promising extensions of the discussed methods toward new materials systems and application fields.

Towards Single‐Crystalline DNA Origami Lattices on Silicon Wafers for Bottom‐Up Nanofabrication - Järvinen, Heini; Parikka, Johannes M.; Rajapaksha, R. P. Thiwangi N.; Keller, Adrian Clemens; Toppari, J. Jussi (Small Structures)
In recent years, nanostructures assembled by DNA have found promising applications in optics, medicine, and sensing. DNA origami in particular provides unique self‐assembly properties, not only enabling a vast variety of functionalization schemes but also presenting a promising route to fabricate large‐scale, bottom‐up nanostructured arrays. This approach has comparable precision to electron beam lithography but avoids slow and expensive patterning steps. However, self‐assembly of lattices with high order and well‐defined periodicity requires careful tuning of the deposition parameters and interactions involved, which has been done mostly on mica so far. As mica is not compatible with standard microfabrication processes, we investigate here the assembly of DNA origami lattices on the most general microfabrication material, that is, silicon wafers, which has turned out to be rather challenging. We study how the forming of polycrystalline 2D‐fishnet‐type lattices is influenced by different incubation conditions and strengths of the origami–origami and origami‐surface interactions, with the aim to create large‐scale single‐crystalline lattices. The lattices are characterized by atomic force microscopy and analyzed for precision of formation, achievable domain size, and surface coverage of well‐formed lattices. Thanks to the silicon substrate, these DNA origami lattices can be further combined with traditional microfabrication processes to turn them, for example, into metamaterials with novel optical properties.

Global Quantitative Analysis of Ligation Reactions in Self‐Assembled DNA Nanostructures at the Single‐Nick Level - Hacker, Konrad; Juricke, Emilia; Münch, Carolin; Suma, Antonio; Keller, Adrian Clemens; Zhang, Yixin (Small)
ABSTRACT Ligation of staple strands in DNA origami nanostructures (DONs) can yield enhanced structural stability in critical environments. This process can be viewed as performing hundreds of parallel reactions programmed on a self‐assembled nanoscale platform. While previous studies have focused on investigating the collective results of the chemical or enzymatic ligation reactions, herein, the global quantitative analysis of individual ligation reactions is achieved using quantitative PCR (qPCR). By mapping enzymatic ligation efficiency on a trapezoidal substructure representing one‐third of a triangular DON, ligation is shown to preferentially occur at the trapezoid edges rather than at inner sites. Excellent agreement between the experimental ligation yields and docking simulations suggests that this is a result of variations in the ligase docking probability. Ligation products involving more than two consecutive sequences can be generated with each enzyme‐catalyzed reaction as an independent event. Interestingly, the sharp contrast between the edges vs. the inner sites has been abolished by changing the reaction conditions and performing the ligation in a DMSO co‐solvent system. This analytic method provides unprecedented insight into the multiple ligation reactions occurring in parallel within complex DONs and will be an invaluable tool in the translation of DONs from the lab to real‐world applications.

Two-electrode electrochemical impedance spectroscopy at polymer/oxide interfaces - Golebiowska, Sandra Alicja; Meinderink, Dennis; Ebbert, Christoph; Kollmann, Sabrina; Neßlinger, Vanessa; Grundmeier, Guido (International Journal of Adhesion and Adhesives)

Influence of negative ions on the stoichiometry and structure of carbon nitride films deposited by reactive magnetron sputtering - Wieschhoff, Christian; Theile-Rasche, Chantal; Wang, Fuzeng; Prib, Michael; Moldt, Viktoria Daniela Dorothea; Grundmeier, Guido; Salas, Nieves López; de los Arcos de Pedro, Maria Teresa (Journal of Applied Physics)
Magnetron-sputtered CNx thin films are primarily employed as hard, low-friction protective and tribological coatings, as solar cells, and for catalytic applications. Lower growth rates and a reduced N content, favoring graphitic sp2 structures, hinder industrial scalability due to prolonged deposition times and produce softer, less dense films with inferior hardness, elasticity, and wear resistance. Carbon nitride films deposited by magnetron sputtering exhibit growth behavior strongly influenced by plasma–surface interactions. However, nitrogen resputtering and reduced film growth rates are commonly attributed to chemical etching by positive ions. We propose an additional, unreported power-dependent mechanism involving negative ions formed at the carbon target. These ions are accelerated through the plasma sheath, reaching the substrate with high kinetic energy and inducing both chemical and physical resputtering. This effect is localized to the geometrical projection of the target, as shown by spatially resolved analysis: ellipsometry reveals thickness reduction, and x-ray photoelectron spectroscopy and Raman spectroscopy indicate nitrogen depletion within this region. Correlation between stoichiometry and structural signatures confirms the decisive role of negative ions in modifying the film composition and microstructure. At the same time, the composition of the gas mixture exerts only a minor effect.

Role of Irradiance in Light-Activated In 2 O 3 Gas Sensors: Why More Light Is Not Always Better - Voth, Sven; Zhao, Zhenyu; Baier, Dominik; Glass, Alexandra; Elgabarty, Hossam; Sandberg, Oskar J.; Grundmeier, Guido; Tiemann, Michael; Smått, Jan-Henrik; Anttu, Nicklas; de los Arcos de Pedro, Maria Teresa; Weinberger, Christian (ACS Sensors)

Influence of deposition temperature and thickness of ALD-TiO2 on planar perovskite solar cell performance - Qudsia, Syeda; Weiss, Alexander; Sirkiä, Saara; Wang, Fuzeng; Rosqvist, Emil; de los Arcos de Pedro, Maria Teresa; Weinberger, Christian; Halme, Janne; Kemell, Marianna; Smått, Jan-Henrik (Applied Surface Science)

The catalyst that stores charge first - Linnemann, Julia; Leppin, Christian (Bunsen-Magazin)
Alkaline oxygen evolution on Co3O4 involves more than adsorption and electron transfer at a fixed surface. The article draws on operando electrochemical quartz crystal microbalance with dissipation monitoring (EQCM-D), surface X-ray diffraction (SXRD), Raman, UV/Vis and impedance spectroscopy. On this basis, it discusses pseudocapacitive oxidation of cobalt ion sites, electrolyte uptake and near-surface transformation, and asks which of these changes are kinetically coupled to electrocatalysis.
Keywords: electrocatalysis; oxygen evolution reaction; cobalt spinel; operando characterization; spectroelectrochemistry

Vancomycin‐Mediated Binding of DNA Origami Nanostructures to Gram‐Positive and Gram‐Negative Bacteria - Coşkuner Leineweber, Özge; Hofmann, Ulrike; Grundmeier, Guido; Zhang, Yixin; Keller, Adrian Clemens (ChemBioChem)
DNA origami nanostructures (DONs) have promising applications in biomedicine and biosensing, which often require their efficient binding to target cells. By immobilizing the glycopeptide antibiotic vancomycin on DONs, DON binding to Gram‐positive and Gram‐negative bacteria can be facilitated. Here, we investigate how this multivalent binding is affected by the number and arrangement of the vancomycin modifications on two‐dimensional DONs. We find that for both Gram‐positive Bacillus subtilis and Gram‐negative Escherichia coli , binding increases with the number of vancomycin modifications per DON. In general, binding to E. coli is stronger than to B. subtilis , which may be attributed to differences in the architectures of the cell envelopes. Interestingly, for both bacteria, the total number of vancomycin modifications appears to be more important than their arrangement, as DONs with 18 vancomycin molecules on one side show similar binding as DONs with 18 vancomycin molecules distributed over both sides. This enables the attachment of multiple probe molecules to the vancomycin‐free side of the DONs for enhancing detection efficiency without compromising binding affinity. These results may thus provide guidelines for the design and synthesis of vancomycin‐modified DONs for antimicrobial drug delivery and pathogen detection.

Ongoing efforts to enhance stability - Keller, Adrian Clemens (Nucleic Acid Insights)
Over the last few decades, a large variety of nucleic acid‑based therapeutic approaches and drug formulations have been developed in the lab, tested in the clinic, and brought to market, ranging from antisense oligonucleotides (ASOs) and siRNAs to aptamer inhibitors and mRNA vaccines, with DNA and RNA nanostructure therapeutics already looming on the horizon. However, being susceptible toward hydrolysis, oxidation, non‑specific binding, and nuclease digestion, unmodified nucleic acids are rapidly degraded in vivo, resulting in poor therapeutic performance. Therefore, several stabilization strategies have been developed in order to protect those fragile molecules against adverse conditions during storage and in the body, while simultaneously accommodating their various mechanisms of action such as cellular uptake, target binding, or translation. These strategies include chemical modifications at the nucleoside level, complexation with proteins and polymers, and encapsulation in lipid nanoparticles (LNPs). Despite this variety of available methods, the field still faces many challenges, and this issue aims to provide an overview of the ongoing efforts to enhance the stability of therapeutic nucleic acids.

Surface-Assisted Assembly of DNA Origami Lattices on Silicon Wafers - Parikka, Johannes; Pothineni, Bhanu Kiran; Järvinen, Heini; Tapio, Kosti; Keller, Adrian; Toppari, J. Jussi (Methods in Molecular Biology)

Rapid assembly of highly ordered DNA origami lattices at mica surfaces - Pothineni, Bhanu Kiran; Barner, Jörg; Grundmeier, Guido; Contreras, David; Castro, Mario; Keller, Adrian (Discover Nano)
Abstract The surface-assisted assembly of DNA origami lattices is a potent method for creating molecular lithography masks. Lattice quality and assembly kinetics are controlled by various environmental parameters, including the employed surface, the assembly temperature, and the ionic composition of the buffer, with optimized parameter combinations resulting in highly ordered lattices that can span surface areas of several cm 2 . Established assembly protocols, however, employ assembly times ranging from hours to days. Here, the assembly of highly ordered hexagonal DNA origami lattices at mica surfaces is observed within few minutes using high-speed atomic force microscopy (HS-AFM). A moderate increase in the DNA origami concentration enables this rapid assembly. While forming a regular lattice takes 10 min at a DNA origami concentration of 4 nM, this time is shortened to about 2 min at a concentration of 6 nM. Increasing the DNA origami concentration any further does not result in shorter assembly times, presumably because DNA origami arrival at the mica surface is diffusion-limited. Over short length scales up to 1 µm, lattice order is independent of the DNA origami concentration. However, at larger length scales of a few microns, a DNA origami concentration of 10 nM yields slightly better order than lower and higher concentrations. Therefore, 10 nM can be considered the optimum concentration for the rapid assembly of highly ordered DNA origami lattices. These results thus represent an important step toward the industrial-scale application of DNA origami-based lithography masks.

DNA origami adsorption at single-crystalline TiO2 surfaces - Xu, Xiaodan; Golebiowska, Sandra Alicja; de los Arcos, Teresa; Grundmeier, Guido; Keller, Adrian (RSC Applied Interfaces)
The immobilization of DNA origami nanostructures on solid surfaces is an important prerequisite for their application in many biosensors. So far, DNA origami immobilization has been investigated in detail only...

DNA Origami Adsorption and Lattice Formation on Different SiOx Surfaces - Pothineni, Bhanu Kiran; Theile-Rasche, Chantal; Müller, Hendrik; Grundmeier, Guido; de los Arcos de Pedro, Maria Teresa; Keller, Adrian (Chemistry – A European Journal)
Self-assembled DNA origami lattices on silicon oxide surfaces have great potential to serve as masks in molecular lithography. However, silicon oxide surfaces come in many different forms and the type and history of the silicon oxide has a large effect on its physicochemical surface properties. Therefore, we here investigate DNA origami lattice formation on differently fabricated SiOx films on silicon wafers after wet-chemical oxidation by RCA1. Despite having similar oxide compositions and hydroxylation states, of all surfaces tested, only thermally grown SiOx performs similarly well as native oxide. For the other SiOx films deposited by plasma-enhanced chemical vapor deposition and magnetron sputtering, DNA origami adsorption is strongly suppressed. This is attributed to an increased surface roughness and a lower oxide density, respectively. Our results demonstrate that the employed SiOx surface may decide over the outcome of an experiment and should be considered as an additional parameter that may require optimization and fine-tuning before high-quality lattices can be assembled. In particular, our observations suggest that efficient DNA origami lattice assembly on SiOx surfaces requires a low surface roughness and a high oxide density.